Physico-mechanical Properties of Low-density GeopolymerMortarSynthesized Using Inexpensive Foam Agent. Issue 1 (November 2020) - Amri, A; Reski, M; Helwani, Z; Aman; Hendri, Y B; Maizir, H; Saputro, S; Wahyuadi, J
Abstract: Low-density geopolymer(LDG) mortars have been synthesized through the use of an inexpensive car-wash foaming agent. LDG mortarswere made by mixing coal fly ash and sand with activator solution of NaOH and Na2 SiO3 . The slurry mixture was then mixed with a thick foam and stirred using a hand mixer. During the stirring process, the ordinary Portland cement (OPC)was added to the mixture as additive. Once homogeneous, the slurry mixture was then poured into mortar molds and left overnight at room temperature before heat treatment at 60 °C for 24 h. The geopolymer mortars formed were then characterized. The density measurement showed that the density of geopolymerdecreased to about half from the original density at the OPC compositions of 5-15% and the activator solution compositions of 20-26%. In this composition range, the highest compressive strength (2.15 MPa) was shown by the LDG synthesized using a 23% activator solution and 15% OPC. Further addition of activator solution decreased the compressive strength due to the increase of porosity. The thermal durability test indicated that the LDG structure was relatively stable up to a temperature of 300 C. A further increase in temperature would cause structural degradation.